PLEASE Strategy for Teaching Writing Viewed from Students' Self-Esteem - Atmojo, Arief Eko Priyo (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This research aims to investigate whether: (1) PLEASE strategy is more effective than RAFT strategy for writing; (2) Students having high self-esteem are better in writing than those having low self-esteem; and (3) There is an interaction between the strategies and the students’ self-esteem. This research was done at a state secondary school located in Sragen, Jawa Tengah, Indonesia. Cluster random sampling was employed to get the sample consisting of two classes. PLEASE strategy was used in the experimental class meanwhile RAFT strategy was employed in the control class. The students in each class were categorized into students having high self-esteem and low self-esteem. Writing test and self-esteem questionnaire were utilized to gather data. Multifactor Analysis of Variance ANOVA 2 x 2 test and Tukey test were employed to analyze the data after normality and homogeneity tests were undergone. The results indicate that: (1) PLEASE strategy is more effective than RAFT strategy for writing; (2) Students having high self-esteem are better in writing than those having low self-esteem; and (3) There is an interaction between the strategies and the students’ self-esteem. It suggests that PLEASE strategy is an effective strategy for writing compared to RAFT strategy. Further researches comparing PLEASE strategy to other strategies, techniques, or methods and collaborating it with media and innovative materials for writing are encouraged.